Hubungan Pengetahuan, Sikap Dan Paparan Media Sosial Youtube Terhadap Perilaku Merokok Pada Remaja SMAIT Bina Bangsa Sejahtera Kota Bogor Tahun 2024 - Syifa, Nadiatus; Aristi, Dela (Journal of Religion and Public Health, 2024)
Smoking is detrimental to health and is commonly practiced by adults and teenagers. In 2019, WHO data shows that 19.2% of students aged 13-15 years used tobacco and more than 8 million deaths were caused by tobacco. This is due to a lack of knowledge aboutthe dangers of smoking and exposure to negative content on social media which can influence teenagers' attitudes towards smoking. This study aims to determine the relationship between knowledge, attitudes and exposure to YouTube social media on smoking behavior among teenagers at SMAIT Bina Bangsa Sejahtera Bogor City with a cross-sectional study design and a sample of 156 people. This research is quantitative research with data collection through questionnaires. The data analysis used in the research was univariate analysis and bivariate analysis using the Chi-square test. The research results showed that the smoking behavior of SMAIT Bina Bangsa Sejahtera teenagers was 30.8% with attitudes supporting smoking at 51.3%, and teenagers who were exposed to negative and positive content on YouTube social media were 85.9%. The results of the analysis showed that there was a relationship between knowledge and attitudes towards smoking behavior. Teenagers are expected to be more careful in receiving information from YouTube social media, choose trusted sources and limit the time they use YouTube each day.Keywords: Attitude, Smoking behavior, YouTube.